2013
DOI: 10.5603/cj.a2016.0049
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and lifestyle in patients pharmacologically treated due to hypertensionally treated due to hypertension.

Abstract: 11 g/d, potassium: 3,808.5 ± 1,265.7 mg/d, calcium: 724.6 ± 413.7 mg/d, and magnesium: 383.9 ± ± 139.3 mg/d. One in 5 (18%) (Cardiol J 2016; 23, 5: 491-496)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 19 publications
2
11
0
6
Order By: Relevance
“…Recent study showed that the intensive antihypertensive medical treatment combined with the lifestyle modification led to the better blood pressure control of hypertensive patients including the elderly (10). Apart from the factors linked to the patient itself that may influence adherence to either medication or healthy lifestyle (11) including depression, low social support and low quality of life, knowledge, beliefs and attitudes towards the hypertension, the patients counseling by their physicians also plays a key role in managing the hypertension. The results of our study demonstrated that only a third to no less than a half of hypertensive patients has been advised by their physician about the appropriate diet, physical activity and smoking cessation that were an obligatory part of a treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Recent study showed that the intensive antihypertensive medical treatment combined with the lifestyle modification led to the better blood pressure control of hypertensive patients including the elderly (10). Apart from the factors linked to the patient itself that may influence adherence to either medication or healthy lifestyle (11) including depression, low social support and low quality of life, knowledge, beliefs and attitudes towards the hypertension, the patients counseling by their physicians also plays a key role in managing the hypertension. The results of our study demonstrated that only a third to no less than a half of hypertensive patients has been advised by their physician about the appropriate diet, physical activity and smoking cessation that were an obligatory part of a treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Spożywanie tej żywności w nadmiarze może również prowadzić do wielu innych przewlekłych chorób niezakaźnych, do których należą m.in. : cukrzyca typu 2, nadciśnienie tętnicze, miażdżyca oraz choroby sercowo-naczyniowe [12,13].…”
Section: Omówienieunclassified
“…Częste spożywanie żywności typu fast food może być przyczyną zwiększonego ryzyka powstawania chorób dietozależnych, takich jak: nadwaga i otyłość, cukrzyca typu 2 oraz nadciśnienie tętnicze [12,13]. Analiza przeprowadzonych badań wykazała, że szczególnie narażo-na na tego typu schorzenia jest młodzież w wieku 16 lat mająca nadwagę, ponieważ najczęściej spożywała produkty typu fast food.…”
Section: Omówienieunclassified
See 1 more Smart Citation
“…Jednym z najczęściej występujących zaburzeń odżywiania okresu rozwojowego jest otyłość prosta [30]. Zaburzenie to jest wynikiem zakłóconej równowagi między energią z pożywienia a jej zużyciem, co w konsekwencji powoduje jej nadmiar i gromadzenie się tkanki tłuszczowej, nadmierny przyrost masy ciała, przekraczający znacznie normy z uwagi na wiek i wzrost dziecka [31][32][33]. Jest to inaczej wynik niewłaściwego działania mecha-nizmów regulujących masę ciała jednostki [34, s. 52].…”
Section: Zagadnienie Wybranych Przewlekłych Zaburzeń Endokrynnychunclassified